2010
DOI: 10.4161/cc.9.12.12048
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cells induce the cancer associated fibroblast phenotype via caveolin-1 degradation: Implications for breast cancer and DCIS therapy with autophagy inhibitors

Abstract: Loss of stromal caveolin 1 (Cav-1) is a novel biomarker for cancer-associated fibroblasts that predicts poor clinical outcome in breast cancer and DCIS patients. We hypothesized that epithelial cancer cells may have the ability to drive Cav-1 downregulation in adjacent normal fibroblasts, thereby promoting the cancer associated fibroblast phenotype. To test this hypothesis directly, here we developed a novel co-culture model employing (i) human breast cancer cells (MCF7), and (ii) immortalized fibroblasts (hTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
239
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 219 publications
(251 citation statements)
references
References 29 publications
12
239
0
Order By: Relevance
“…Chen et al showed that reduced cav-1 expression correlated with increased ROS production in the adventitia of hypertensive PA [36] . Martinez-Outschoorn et al demonstrated that a loss of stromal cav-1 in fibroblasts was sufficient to induce ROS production and oxidative stress, indicating that a loss of cav-1 provided a feed-forward mechanism for promoting oxidative stress and the autophagic program [37][38][39] . Zhang et al showed that glucose-induced ROS generation was significantly attenuated by the chemical disruption of caveolae in knockout mesangial cells [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al showed that reduced cav-1 expression correlated with increased ROS production in the adventitia of hypertensive PA [36] . Martinez-Outschoorn et al demonstrated that a loss of stromal cav-1 in fibroblasts was sufficient to induce ROS production and oxidative stress, indicating that a loss of cav-1 provided a feed-forward mechanism for promoting oxidative stress and the autophagic program [37][38][39] . Zhang et al showed that glucose-induced ROS generation was significantly attenuated by the chemical disruption of caveolae in knockout mesangial cells [30] .…”
Section: Discussionmentioning
confidence: 99%
“…The reverse Warburg effect in estrogen receptor positive breast cancers includes the metabolic interaction between tumor cells and stromal cells. Thereby, cancer cells promote the metabolic reprogramming of stromal cells such as fibroblasts into cancer-associated fibroblasts [58]. Specifically, fibroblasts co-cultured with breast cancer cells displayed decreased caveolin 1 expression, and induction of HIF1 and NF B [59].…”
Section: Estrogen Receptor Positive Breast Cancermentioning
confidence: 99%
“…As ketone bodies are preferentially used only during periods of starvation, we envision that limited RePORT RePORT Cav-1 expression under these co-culture conditions is due to its autophagic digestion, which is lysosome-dependent. 6,7 Fibroblasts overexpressing ketogenic enzymes induce mitochondrial biogenesis in MCF7 cells, as well as cell growth. To examine the paracrine effects of HMGCS2-and BDH1-overexpressing fibroblasts on adjacent cancer cells, they were coculultured with MCF7 cells under low mitogen conditions.…”
Section: Introductionmentioning
confidence: 99%